SN 2018gjx reveals that some SNe Ibn are SNe IIb exploding in dense circumstellar material. Issue 1 (25th September 2020) - Prentice, S J; Maguire, K; Boian, I; Groh, J; Anderson, J; Barbarino, C; Bostroem, K A; Burke, J; Clark, P; Dong, Y; Fraser, M; Galbany, L; et al.
ABSTRACT: We present the data and analysis of SN 2018gjx, an unusual low-luminosity transient with three distinct spectroscopic phases. Phase I shows a hot blue spectrum with signatures of ionized circumstellar material (CSM), Phase II has the appearance of broad SN features, consistent with those seen in a Type IIb supernova at maximum light, and Phase III is that of a supernova interacting with helium-rich CSM, similar to a Type Ibn supernova. This event provides an apparently rare opportunity to view the inner workings of an interacting supernova. The observed properties can be explained by the explosion of a star in an aspherical CSM. The initial light is emitted from an extended CSM (∼4000 R ⊙ ), which ionizes the exterior unshocked material. Some days after, the SN photosphere envelops this region, leading to the appearance of a SN IIb. Over time, the photosphere recedes in velocity space, revealing interaction between the supernova ejecta and the CSM that partially obscures the supernova nebular phase. Modelling of the initial spectrum reveals a surface composition consistent with compact H-deficient Wolf–Rayet and Luminous Blue Variable (LBV) stars. Such configurations may not be unusual, with SNe IIb being known to have signs of interaction so at least some SNe IIb and SNe Ibn may be the same phenomena viewed from different angles, or possibly with differing CSM configurations.